Measuring subjectively experienced time in usability and user experience testing scenarios. Issue 138 (June 2020) - Trukenbrod, Anna K.; Backhaus, Nils; Thomaschke, Roland
Highlights: Subjectively experienced time is an important aspect of UX. It describes the subjective evaluation of temporal attributes of an in- teraction. We show that it is based on time perception and integrated into the overall UX. We provide a ready-to-use way of measuring subjectively experienced time. Abstract: Duration perception influences decision and evaluation processes in daily life. Nevertheless, subjectively experienced time is not commonly considered in usability and user experience (UX) testing scenarios. In this paper, we introduce an easy way to measure subjectively experienced time (SXT) and integrate it into a framework of UX, both theoretically and empirically. In two studies ( N = 62 and N = 80 ), we show that SXT can be evaluated by users after solving tasks on a website. Moreover, we show that it correlates substantially with components of UX but that it is not redundant to common UX measures. Additionally, we show that varying aspects of the website (usability) and the evaluation task (think aloud) show similar effects on both SXT and UX measures. Our results suggest that SXT is partly based on the estimated clock time as distortions in estimations translate into subjectively experienced time. We conclude that users perceive time during an ongoing interaction with a technical device, that they evaluate it, and integrate this evaluation into their UX evaluation. Hence, the presented way of measuring SXT can be handy for UX practitioners to understand how objective temporal characteristics of the interaction translate into UX, especially when designing temporal aspects of interactions to elicit a positive UX.